Acousto-optic sensor based on fibre laser dynamics / Pua Chang Hong - Pua, Chang Hong (2012)
All these years, a lot of attempts to build an unassisted optical microphone have failed due to the poor acoustic impedances matching of air and fibre. Although there are theoretical works support that unassisted optical microphones is possible, however not much experimental work has been published to support the argument. This thesis presents an unassisted fibre optic acoustic sensor operate based on the fibre laser dynamic behaviours that overcomes the problem of the acoustic impedance mismatch between air and fibre. Fibre laser dynamic behaviours which are sensitive to acoustic waves are chosen to work as the basic principle of the acousto-optic sensor setup. The behaviours of the fibre laser dynamic are studied on both theoretical and experimental. The experimental results show that the fibre laser is sensitive to the acoustic waves where the incident acoustic waves will cause the fluctuation of the optical output power. The fluctuation amplitude and frequency of the fibre laser is dependent on the acoustic waves amplitude, frequency, and the fibre laser parameters such as pump power, gain, and cavity length. Those relations are studied intensively to understand the operation of the optical microphone. As for sensitivity enhancement and noise reduction, dual wavelength fibre laser is proposed to sense the acoustic waves intensity which below the triggering level of laser dynamics. Mode competition between two difference wavelengths has further enhanced the sensitivity level of the design optical microphone. Besides that, the mode hopping effect due to the mode competition has reduced the high frequency spiking and noise significantly producing better acoustic signal measurement in low frequency domain.